2020
DOI: 10.1177/0003134820933251
|View full text |Cite
|
Sign up to set email alerts
|

The Provision of Acute Pediatric Surgical Care by Adult Acute Care General Surgeons

Abstract: Background At our hospital, acute surgical care of children aged 6 and older is managed by adult acute care surgeons. Previously published data from a 10-year experience with this model demonstrated no differences in outcomes when compared with pediatric surgical benchmark data. This study assesses for the effects of a learning curve in the care of pediatric patients by comparing outcomes of patients treated in the first three years with those treated in the last 3 years during a 10-year experience with this m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Prior reports have suggested that favorable attitudes to laparoscopy can be developed within institutions through specialized courses, especially those involving simulation-based training. 36-38 A previous center reported a marked decrease in laparotomy and increase in laparoscopy in dealing with pediatric abdominal trauma as the surgical teams became familiar with the hospital’s new minimally invasive surgery capability. 27…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior reports have suggested that favorable attitudes to laparoscopy can be developed within institutions through specialized courses, especially those involving simulation-based training. 36-38 A previous center reported a marked decrease in laparotomy and increase in laparoscopy in dealing with pediatric abdominal trauma as the surgical teams became familiar with the hospital’s new minimally invasive surgery capability. 27…”
Section: Discussionmentioning
confidence: 99%
“…Prior reports have suggested that favorable attitudes to laparoscopy can be developed within institutions through specialized courses, especially those involving simulation-based training. [36][37][38] A previous center reported a marked decrease in laparotomy and increase in laparoscopy in dealing with pediatric abdominal trauma as the surgical teams became familiar with the hospital's new minimally invasive surgery capability. 27 Laparoscopy for pediatric patients has many purported benefits including avoidance of a non-therapeutic laparotomy, decreased hospital LOS, as well as improved longand short-term morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…36 The COVID-19 pandemic has placed strains on the health care workforce and there is evidence that clinicians are reducing their hours and retiring early in response to burnout. 37 The literature describes many possible solutions for this potential shortage of trained pediatric staff, such as clinician cross training within an institution among adult and pediatric practitioners, 38,39 knowledge sharing among specialized practitioners like child psychologists, [40][41][42] telemedicine consultation for rural and remote areas, 43 primary care providers taking on specialist roles, 44 and encouraging institutions to support clinicians who choose to work in pediatric specialties with added incentives. 45 Additional supports for the mental health of practising clinicians may also be helpful in addressing chronic clinician burnout.…”
Section: Health Human Resource Managementmentioning
confidence: 99%